Sieć teletransmisyjna Interpolu jako narzędzie międzynarodowej współpracy policyjnej - Szumski, Adrian (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
The Interpol belongs to key international organizations that are engaged in widely comprehended cooperation between police forces. One of the basic forms of activity of this organization is exchange of information between General Secretariat and National Central Bureaus. At present the exchange of data takes place with global police communication network I-24/7, which enables sending information in real-time and also provides an access to other functions that are important to collect criminal information. The possibilities of I-24/7 network enable to increase considerably the effectiveness of actions against criminality.
Keywords: communication network; criminality; General Secretariat; I-24/7; information; Interpol